The Relationship between Mothers' Breastfeeding Self-Efficacy Perceptions and Breastfeeding Success in Postpartum Period - Emine Efe; Fatma Çalışkan; Şevkiye Dikmen (Dokuz Eylul University, 2021)
Background: Breastfeeding is the safest and healthiest way to feed a baby. It contributes to the improvement of the health consequences of the mother and her baby. Objective: This study was planned as a descriptive comparative study to investigate the relationship between breastfeeding self-efficacy perceptions and breastfeeding success of mothers in the postpartum period. Method: The study sample of a university hospital in the south of Turkey lies at the Maternity Service has created 102 healthy female patient who had recently given birth. As a data collection tool; Descriptive data form, Breastfeeding Self-Efficacy Scale-short form, LATCH Breastfeeding Assessment Tool was used. Face-to-face interview method was used to collect descriptive data and breastfeeding self-efficacy scale data. The LATCH Breastfeeding Assessment Tool was evaluated using the observation method at the time of breastfeeding. Results: It was determined that 47.1% of the mothers within the scope of the study were 26-33 years old, 38.2% were primary school graduates, 68.6% had cesarean section and 30.4% had their first birth. Breastfeeding self-efficacy mean score of mothers was 57.30 ± 10.46 and breastfeeding success mean score was 8.38 ± 1.53. There was no statistically significant relationship between breastfeeding self-efficacy and breastfeeding success of the mothers (p = .157, r = .14). A significant correlation was found between mothers' number of children and Breastfeeding Self-Efficacy Scale and LATCH Breastfeeding Assessment Tool scores (p <.05). It was determined that as the number of children increased, breastfeeding self-efficacy and breastfeeding success of mothers increased. Conclusion: It is thought that breastfeeding success and breastfeeding self-efficacy of mothers who support newly mothers by breastfeeding health professionals and family relatives will increase.